Di Balik Layar Internet: Peran Self-Esteem dan Peer Attachment terhadap Problematic Internet Use (PIU) pada Dewasa Muda di Kabupaten Karawang - Yayah Rokayah; Puspa Rahayu Utami Rahman; Anggun Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Technological developments have made the internet an inseparable part of young adults’ daily lives, particularly in communication, entertainment, information seeking, and social interaction activities. Excessive and uncontrollable internet use may lead to Problematic Internet Use (PIU). This study aimed to determine the role of self-esteem and peer attachment on Problematic Internet Use (PIU) among young adults in Karawang Regency. This study used a quantitative approach with multiple linear regression analysis using IBM SPSS Statistics 25.0. The sampling technique used convenience sampling with 385 young adult internet users aged 18–25 years living in Karawang Regency. The instruments used in this study were the Rosenberg Self-Esteem Scale (RSES), Inventory of Parent and Peer Attachment (IPPA), and Problematic Internet Use Questionnaire (PIUQ). The partial test results showed that self-esteem had no significant effect on Problematic Internet Use (PIU) with a significance value of 0.456 (p>0.05), while peer attachment had a significant negative effect on Problematic Internet Use (PIU) with a significance value of 0.000 (p<0.05). The simultaneous test results showed that self-esteem and peer attachment simultaneously had a significant effect on Problematic Internet Use (PIU) with an F value of 56.355 and a significance value of 0.000 (p<0.05). The coefficient of determination test showed an R Square value of 0.228, indicating that self-esteem and peer attachment contributed 22.8% to Problematic Internet Use (PIU). This study showed that peer attachment was more dominant in influencing Problematic Internet Use (PIU) among young adults in Karawang Regency